Sistem Pengawasan Perilaku Pengemudi Berbasis IoT Dengan Pemanfaatan LiDAR dan GPS Untuk Meningkatkan Keselamatan Berkendara - Helmi Wibowo; Faza Asfarin Ajrun Adhim (P3M Politeknik Negeri Cilacap, 2025)
In 2022, a total of 139,258 traffic accidents occurred in Indonesia, encompassing all types of incidents, from minor to fatal. The high number of accidents, particularly those caused by speeding and unsafe following distances, highlights the need for a system capable of automatically monitoring and intervening in driver behavior. This study aims to develop an IoT-based control and monitoring system that not only detects violations such as overspeeding and insufficient following distance but also provides direct intervention in vehicle speed. The system utilizes an Arduino Mega and ESP32, equipped with GPS and LiDAR sensors, along with a DAC output to limit the accelerator pedal voltage when repeated violations are detected. Testing was conducted to evaluate sensor accuracy, IoT performance, and the effectiveness of speed intervention. The results showed a 100% success rate in five speed intervention tests, good sensor accuracy, and IoT notifications successfully delivered with an average delay of 5.9 seconds. The system proved to be effective and feasible as a technology-based solution to enhance driving safety.